2021
DOI: 10.1097/icu.0000000000000801
|View full text |Cite
|
Sign up to set email alerts
|

Retinal and choroidal manifestations of COVID-19

Abstract: Purpose of reviewThe novel coronavirus disease in 2019 (COVID-19) has a wide range of systemic manifestations. Ocular manifestations are now well recognized, with conjunctivitis being the most common. Posterior segment involvement is uncommon and has mainly been described in case reports. This review provides an overview of the posterior segment involvement of COVID-19. Recent findingsSevere acute respiratory syndrome coronavirus 2 affects the retina and the choroid through either direct entry or triggering an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…A recent review confirmed that the majority of the retinal findings in COVID-19 patients were cotton wool spots, flame-shaped intraretinal hemorrhages, PAMM, AMN, or retinal vein occlusions. Rarely, inflammation involving the retina or the choroid, or reactivation of previously quiescent uveitis, may also be seen [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent review confirmed that the majority of the retinal findings in COVID-19 patients were cotton wool spots, flame-shaped intraretinal hemorrhages, PAMM, AMN, or retinal vein occlusions. Rarely, inflammation involving the retina or the choroid, or reactivation of previously quiescent uveitis, may also be seen [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chorioretinitis is a common finding in systemic or local infectious and inflammatory conditions and is also reported to be caused by SARS-CoV-2. The inflammatory effect of COVID-19 is supposed as the mechanism of its influence on this highly vascularized tissue, choroid, resulting in chorioretinal inflammation ( 52 ). There are very few case reports in this regard, reporting reactivation of serpiginous choroiditis 2 weeks after COVID-19 ( 53 ), chorioretinal disease ( 54 ), and bilateral ampiginous choroiditis 1 week after SAR-CoV-2 infection ( 55 ).…”
Section: Resultsmentioning
confidence: 99%
“…So, in principle, choroidal and retinal vessels could be affected by COVID‐19. In fact, recent studies reported microvascular and macrovascular retinal and choroidal changes in cases with COVID‐19 3,7–8 . Although such involvements for choroidal vessels are not clinically supported so far, subclinical injuries from cytokine storm to these vessels are quite possible and might be a risk factor for SCH in patients undergoing intraocular surgery during the recovery phase of COVID‐19.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, recent studies reported microvascular and macrovascular retinal and choroidal changes in cases with COVID‐19. 3 , 7 , 8 Although such involvements for choroidal vessels are not clinically supported so far, subclinical injuries from cytokine storm to these vessels are quite possible and might be a risk factor for SCH in patients undergoing intraocular surgery during the recovery phase of COVID‐19. This assumption is partly supported by the lack of known systemic or ocular risk factors of SCH in our patients and also their recent evident infection with COVID‐19.…”
Section: Discussionmentioning
confidence: 99%